Implementasi Peraturan Menteri Kesehatan Nomor 18 Tahun 2020 Tentang Pengelolaan Limbah Medis Fasilitas Pelayanan Kesehatan Berbasis Wilayah pada Puskesmas Padang Bulan Medan - Romi Indra Cahaya Debataraja; Budi Hartono; Maksum Syahri Lubis (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The objectives of this study are to analyse the implementation and to identify the factors that influence the implementation of the Minister of Health regulation number 18 of 2020 regarding the management of medical waste in area-based health care facilities at the Public Health Center, Padang Bulan Medan. This study applies Edward III's Theory. This study applied qualitative descriptive approach. The informants in this study were the head of the community health center, management of medical waste, and four employees of community health center. The data collection techniques in this study were observation, interviews, and documentation. The data analysis technique in this research used the theory of Miles, Huberman, and Saldana (2014). The results showed that the Public Health Center in Padang Bulan implemented the Ministry of Health Regulation No. 18 of 2020 as seen from the good communication between the head and the employees of the public health center, the resources owned by the public health center in the form of safety boxes, plastic-coated trash cans, and environmental sanitation workers, waste management in an efficient manner in internal and external, Standard operating procedures owned by the community health centers, and recording and reporting the amount of waste every month. The factors that influence the implementation were the commitment of the head of the community health center and employees.